Tuning of multivariable decentralized controllers through the ultimate-point method - Campestrini, Lucíola (2011)
A successful method for tuning single-loop PID controllers is the ultimate-point method. This method is based on the identification of the ultimate point of the process’ frequency response followed by its shifting, through appropriate choices of the controller’s parameters, to a specified location of the complex plane. This paper presents an extension of the ultimate-point method to the tuning of decentralized controllers for multivariable processes.